Preliminary Survey Data From an App-Delivered Hypnosis Intervention for Smoking Cessation - Cameron T. Alldredge; Vanessa Muñiz; Vindhya Ekanayake; Gary R. Elkins (SAGE Publishing, 2024)
Introduction: Hypnosis-based apps geared toward smoking cessation are among the most downloaded by individuals wanting to reduce or stop smoking. However, to date, there are few evaluations regarding the use or efficacy of hypnosis apps for smoking cessation. Finito is an empirically-based mHealth app developed by Mindset Health designed to provide users with a three-week hypnotherapy program to quit smoking. This study aimed to examine demographic and clinical characteristics of Finito app users and conduct a preliminary analysis of survey data from participants of the program. Method: Finito app users were asked to voluntarily complete an online survey regarding their experience with the program, current smoking habits, app usability, relevant improvement, and demographic information. Retrospective data analyses were conducted to provide descriptive and inferential findings from the responses. Results: A total of 120 individuals responded to the survey. Respondents originated from over five different countries and approximately 72.5% reported completing the full Finito program. Approximately 58.3% of participants reported that they accomplished their goal with Finito with 50.8% of all respondents reporting that they quit smoking and an additional 25.8% reporting that their smoking was reduced. Among a variety of secondary outcomes, saving money was the most frequently reported secondary benefit with 46.7% of respondents endorsing that item. Conclusion: Our preliminary survey results suggest that Finito may be a useful, pleasant, and cost-effective tool in a patient's journey to quit smoking. The majority of app users reported that they achieved their goal with Finito and completion of the program was associated with goal achievement. The Finito app may be effective in the dissemination and delivery of a helpful hypnotherapy intervention across a diverse population.